2022
DOI: 10.1007/s40747-022-00691-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and selection of green suppliers for papermaking enterprises using the interval basic probability assignment-based intuitionistic fuzzy set

Abstract: With the vigorous development of the global economy, modern enterprises have agreed to implement green supply chain management. The evaluation and selection of green suppliers plays a vital role in successful green supply chain management. As a multi-attribute group decision-making green supplier selection problem, it is difficult to fully describe the evaluation factors using precise numerical values and classical fuzzy sets, so it cannot assist enterprise managers in making completely reasonable decisions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The green building-related evaluation indexes were re-selected, and finally, a building greenness evaluation index system containing 6 primary indexes and 18 secondary indexes was established (Lu et al. , 2022; Kang et al. , 2022; Chen et al.…”
Section: Establishment Of Green Building Greenness Evaluation Index S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The green building-related evaluation indexes were re-selected, and finally, a building greenness evaluation index system containing 6 primary indexes and 18 secondary indexes was established (Lu et al. , 2022; Kang et al. , 2022; Chen et al.…”
Section: Establishment Of Green Building Greenness Evaluation Index S...mentioning
confidence: 99%
“…By reading a lot of literature, we refer to the new Chinese version of GB/T50378-2019 "Green Building Evaluation Standard" and the green building evaluation models proposed by domestic and foreign scholars. The green building-related evaluation indexes were reselected, and finally, a building greenness evaluation index system containing 6 primary indexes and 18 secondary indexes was established (Lu et al, 2022;Kang et al, 2022;Chen et al, 2022a, b). The established green building greenness evaluation index system is shown in Figure 2.…”
Section: K 5210mentioning
confidence: 99%
“…Verma et al [20] show that green supplier selection will help in increasing the environmental sustainability of a company. Kang et al [21] found that the evaluation and selection of green suppliers play a vital role in successful green supply chain management. Segura et al [22] also argued that suppliers play a key role in supply chain management which involves evaluation for supplier selection problems, as well as other complex issues that companies should take into account.…”
Section: Introductionmentioning
confidence: 99%